THE CONSEQUENCES OF THE INTERNET FOR POLITICS - V. P. Terin (Vestnik MGIMO-Universiteta, 2013)
The managerial importance of the internet increasingly attracts political forces. The article deals with the internet as a political resource referring to President Obama involving the American people in his fight with the Republicans in Congress, and other similar issues of general concern. The author analyses the use of information and communication technologies in the USA political life and also makes conclusions about global tendencies of the information technologies development. After Barack Obama was elected president in the USA, information technologies have gained political significance. The author believes that Obama plans his second term in power as a turning point for the development of the country which is connected to the economic development. USA political strategy is global; the same is true for the information sphere. Barack Obama influences global politics as if it were operation system of the computer. Thus the author believes that such problems as determination of the driving forces of the Arab spring and real reasons for the USA refusal to sign new telecommunications treaty at the ITU conference in Dubai deserve special analysis taking into account the role of the information and communication technologies.